Coloring Use in Film Tenggelamnya Kapal Van Der Wijck (Semiotic Analysis of Christian Metz) - moch ilham auliyak (ROLLING, 2021)
The film's Tenggelamnya Kapal Van Der Wijck is a film-drama and romance genre that raises the love story of a young man named Zainuddin to Hayati who is blocked from customary rule. There is a prominent use of coloring in the film Tenggelamnya Kapal Van Der Wijck. Color selection was determined during the pre-production process as the identity of the film. Researchers examine the application of coloring in the film Tenggelamnya Kapal Van Der Wijck aims to determine the process of the message that is contained in the film. Research discussing the application of coloring is analyzed by the semiotics approach of Christian Metz film among others descriptive Syntagma, parallel Syntagma, and alternate Syntagma. Research on the application of coloring the film's Tenggelamnya Kapal Van Der Wijck also used color theory to reinforce the perception of the dominant use of color in the film. This research uses qualitative descriptive methods with data collection techniques in the form of observations, documentation, and library studies. The results of the research can be proved that the color tendencies in the film's Tenggelamnya Kapal Van Der Wijck were conceptualized as a marker of space, time, and scene, and influenced the character's condition and atmosphere in the scene.